Lebenswelt und Wissenschaft Zum Spannungsverhältnis zweier Erfahrungsweisen - Schiemann, Gregor 1954- (De Gruyter, 2021)
Although the scientification of society continues to advance, science and the lifeworld still exist with and against each other as different modes of experience. This book demonstrates their structural differences by discussing numerous examples. The studies are guided by concepts, the theory of science, and phenomenology, and are based on a concept of science that also encompasses the technical sciences